An evaluation of superhydrophilic surfaces of dental implants - a systematic review and meta-analysis - Arkadiusz Makowiecki; Jakub Hadzik; Artur Błaszczyszyn; Tomasz Gedrange; Marzena Dominiak (BMC, 2019)
Abstract Background The characteristics of a dental implant surface have a decisive influence on the process of osseointegration. According to the current state of knowledge, surface modification can not only affect the morphology of cells, and in this way have a positive impact on osseointegration. Methods The objective of this study was to compare survival rates and marginal bone loss as well as assess the degree of stability of Straumann SLAactive® and Thomenn Incell® implants with a superhydrophilic surface. Authors present review of data published between 01.01.2008 and 12.31.2016 that was found in PubMed/MEDLINE internet database, An Internet search of databases produced a total of 1230 studies, 20 publications were finally selected for the present study based on the established selection and exclusion criteria. Results The statistical analysis was performed. A Cumulative Implant Survival Rate (CSR%) was 98.5%, Marginal bone loss (MBL) after 6 months was M = 0.60 mm and 0.6 5 mm after 12 months and secondary stability in a group Thommen implants M = 71.3 ISQ and M = 75.2 ISQ in group of Straumann. Conclusion Despite certain differences in the values of the studied parameters, both of the systems, i.e. Thommen Inicell and Straumann SLActive, demonstrated a high survival rate, a high level of implant stability and low marginal bone loss.